Exposure to avian coronavirus vaccines is associated with increased levels of SARS‐CoV‐2‐cross‐reactive antibodies. Issue 12 (23rd July 2022) - Ardicli, Ozge; Carli, K. Tayfun; Satitsuksanoa, Pattraporn; Dreher, Anita; Cusini, Alexia; Hutter, Sandra; Mirer, David; Rückert, Beate; Jonsdottir, Hulda R.; Weber, Benjamin; Cervia, Carlo; Akdis, Mubeccel; et al.
Abstract: Background: Although avian coronavirus infectious bronchitis virus (IBV) and SARS‐CoV‐2 belong to different genera of the Coronaviridae family, exposure to IBV may result in the development of cross‐reactive antibodies to SARS‐CoV‐2 due to homologous epitopes. We aimed to investigate whether antibody responses to IBV cross‐react with SARS‐CoV‐2 in poultry farm personnel who are occupationally exposed to aerosolized IBV vaccines. Methods: We analyzed sera from poultry farm personnel, COVID‐19 patients, and pre‐pandemic controls. IgG levels against the SARS‐CoV‐2 antigens S1, RBD, S2, and N and peptides corresponding to the SARS‐CoV‐2 ORF3a, N, and S proteins as well as whole virus antigens of the four major S1‐genotypes 4/91, IS/1494/06, M41, and D274 of IBV were investigated by in‐house ELISAs. Moreover, live‐virus neutralization test (VNT) was performed. Results: A subgroup of poultry farm personnel showed elevated levels of specific IgG for all tested SARS‐CoV‐2 antigens compared with pre‐pandemic controls. Moreover, poultry farm personnel, COVID‐19 patients, and pre‐pandemic controls showed specific IgG antibodies against IBV strains. These antibody titers were higher in long‐term vaccine implementers. We observed a strong correlation between IBV‐specific IgG and SARS‐CoV‐2 S1‐, RBD‐, S2‐, and N‐specific IgG in poultry farm personnel compared with pre‐pandemic controls and COVID‐19 patients. However, no neutralization was observed for these cross‐reactive antibodies from poultry farm personnel using the VNT. Conclusion: We report here for the first time the detection of cross‐reactive IgG antibodies against SARS‐CoV‐2 antigens in humans exposed to IBV vaccines. These findings may be useful for further studies on the adaptive immunity against COVID‐19. Abstract : IBV‐ and SARS‐CoV‐2‐specific IgG antibodies were measured in poultry farm personnel, COVID‐19 patients and pre‐pandemic controls. Elevated levels of IBV‐ and SARS‐CoV‐2‐sIgG were detected in a subgroup of poultry farm personnel, in particular among vaccine implementers. Longer work experience in vaccine implementers was associated with higher levels of S1‐, RBD‐, 4/91‐, IS/1494/06‐, M41‐, D274‐sIgG. Significant positive correlations were observed between IBV‐specific IgG and SARS‐CoV‐2‐specific IgG in poultry farm personnel but not in COVID‐19 patients or pre‐pandemic controls. Abbreviations: COVID‐19, coronavirus disease 2019; IBV, avian coronavirus infectious bronchitis virus; RBD, receptor binding domain; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus‐2; sIgG, antigen‐specific immunoglobulin G